Design of stationary computed tomography baggage scanner with π-angle sparsity and compressed-sensing reconstruction: simulation study. (1st January 2023) - Shim, J.; Jeon, D.; Jung, Y.; Yang, H.; Lim, Y.; Cho, H.; Seo, C.; Choi, K.Y.; Sone, C.S.; Jang, M.S.
Abstract: Continuing our research on X-ray R&D for aviation security, we designed a novel stationary computed tomography (SCT) baggage scanner with π-angle sparsity, comprising several dozen pairs of nanotube-based X-ray source and linear array-type detector placed within a scan angle of 180° at an equiangular distance. Simultaneously, we developed a reconstruction method for the specific configuration adopting an iterative algorithm based on the popular compressed-sensing (CS) scheme. To validate the efficacy of the proposed SCT design, we conducted a series of simulations using a numerical baggage phantom before its practical implementation. The results showed that the proposed SCT design and corresponding reconstruction method significantly reduced the streak artifacts appearing in the filtered-backprojection (FBP) reconstruction, thereby considerably improving the image quality. The contrast-to-noise ratio evaluated under a test condition of 180°/P20/CS was approximately 16.2, approximately 4.7 and 1.1 times larger than those for 360°/P20/FBP and 360°/P20/CS, respectively. The proposed SCT design enables saving scan time, improving image quality, and restricting radiation exposure zone.